Central cemetery, Vienna - Unknown (photographer):::Creator::::::::::::; Harper, T. R. (author):::Contributor::::::::::::
Photograph of the Central Cemetery in Vienna, showing the area of the tombs of Beethoven and Schubert, and the monument to Mozart; plate from a book by T.R. Harper, p. 277-278 from the chapter Some Masters of Music.